Efektifitas Model Pembelajaran Kooperatif Tipe STAD Dalam Mengembangkan Self Efficacy Matematika - Ismunandar, Andi Auliya; Suriyati, Suriyati; Nurjannah, Nurjannah (Jumper: Journal of Educational Multidisciplinary Research, 2023)
The purpose of this study was to evaluate the effectiveness of the Student Teams Achievement Division (STAD) cooperative learning model in increasing the self-efficacy level of mathematicians in class VIII B SMPN 20 Sinjai. This research is a quantitative research with a Pre-Experimental Design approach (One-Group Pretest-Posttest Design). A total of 32 class VIII B students at SMP Negeri 20 Sinjai were included in simple random sampling for the spring semester of the 2021/2022 academic year. The data collection methodology uses measures of self-efficacy and student learning outcomes. Data analysis using inferential and descriptive statistics. Previously, a prerequisite test was carried out using the normality test and homogeneity test. The research findings show that, according to the descriptive analysis, the average score for a woman's mathematical self-efficacy is 61.68 and she is in the top category. However, the average score of the student learning outcomes test after the STAD cooperative learning model was applied was 89.84 and was in the upper category. As the last step, based on statistical inference analysis with a significance level of sig. (2-tailed), ie 0.000 0.05, H0 is rejected, and Ha is accepted. Based on the results of the study it can be concluded that the STAD type cooperative learning model is effective in increasing the mathematical self-efficacy of class VIII B students of SMP Negeri 20 Sinjai.